Dinamika Historis dalam Proses Pewahyuan Al-Qur’an: Kajian Terhadap Tahapan Turunnya Wahyu - Arina Mana Sikana; Bilqis Yazmil Faza As Sakinah; Dhamar Ibrahim Kadista Putra; Mohamad Salik (Jurnal Budi Pekerti Agama Islam, 2026)
This study focuses on the historical dynamics of the Qur’anic revelation process to examine in greater depth the relationship between the gradual nature of the revelation process and the social conditions of Arab society, particularly during the Mecca and Medina periods. The method used in this study is library research, utilizing sources such as scientific journals, books, and articles relevant to the research topic. The findings indicate that revelation was received gradually over 23 years, in accordance with the development of Islamic da’wah and the social dynamics of the time. During the Mecca period, the revelations focused on the teachings of tawhid, creed, and ethics, as Arab society was still in a state of jahiliyyah. In the Medina period, the focus shifted to the rituals of worship and Islamic law as the Islamic community in Medina grew. Furthermore, some verses of the Qur’an were revealed in response to issues within society. This indicates a connection between revelation and the socio-historical context during the process of revelation. A deeper understanding of the process of revelation requires further study, and this research is expected to provide a more profound understanding of the Qur’anic revelation process through a historical approach.